2021
DOI: 10.1016/j.invent.2021.100472
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 news valence effects on emotion and its modulation by a relaxation: A randomized online experiment during COVID-19 pandemic

Abstract: This study evaluated how news with positive and negative content about COVID-19, as well as a relaxation pause, affect the emotional state. We also investigated the association between emotional state and practicing meditation/yoga, physical activity or having a mental disease. For that, a sample of 717 participants, recruited through social media, were randomly assigned to listen to negative or positive news about COVID-19. After that, both groups were guided through a short relaxation pause. Their emotional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
1
2
0
1
Order By: Relevance
“…Watching a film with negative valence induces participants to be in a more negative emotional state than at baseline. These results are in line with previous studies of our research group using only audios reporting news with positive and negative contents ( Bazán et al, 2021a , b ). There is a variety of ways to elicit emotion; for example, Westermann et al (1996) carried out many procedures using films, imagination strategies, storytelling, music, feedback, social interaction, posed facial expressions, and others.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Watching a film with negative valence induces participants to be in a more negative emotional state than at baseline. These results are in line with previous studies of our research group using only audios reporting news with positive and negative contents ( Bazán et al, 2021a , b ). There is a variety of ways to elicit emotion; for example, Westermann et al (1996) carried out many procedures using films, imagination strategies, storytelling, music, feedback, social interaction, posed facial expressions, and others.…”
Section: Discussionsupporting
confidence: 93%
“…Negative news worsened participants’ emotional state, while positive news improved it. These results were found both for the general population ( Bazán et al, 2021b ) and for healthcare professionals ( Bazán et al, 2021a ).…”
Section: Introductionmentioning
confidence: 60%
“…When compared, it was seen that vaccination rates decreased with the emergence of negative news. Apart from this, studies conducted in the USA (Stainback et al, 2020) and Israel (Bazán et al, 2021) during the COVID-19 epidemic have revealed that negative news can negatively affect people. In short, the causes of problems can be discussed better with the help of the news, and the public's awareness can be raised by constantly focusing on certain issues (Gollust and Lantz, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A amostra foi composta predominantemente por mulheres, o que condiz com estudos que apontam maior disposição de mulheres em pesquisas online (216,217), o que também tem sido observado em outros estudos online do nosso grupo com recrutamento aberto para ambos os sexos (218,219) Em relação ao pareamento entre jovens e idosos das habilidades manuais, idosos apresentaram maior lentidão no teste motor do 9HPT para ambas as mãos, estando dentro dos dados normativos deste teste para essa faixa etária (195,196). Desta forma, o desempenho de nossa amostra é comparável com aquele obtido na aplicação (e desenvolvimento) desse teste.…”
Section: Casuísticaunclassified